Assessment of Dihydro[1, 3]oxazine‐Fused Isoflavone and 4‐Thionoisoflavone Hybrids as Antibacterials. Issue 29 (11th August 2021) - Lathwal, Ankit; Ali, Asghar; Uddin, Amad; Khan, Nashra Shareef; Sheehan, Gerard; Kavanagh, Kevin; Haq, Qazi Mohd. Rizwanul; Abid, Mohammad; Nath, Mahendra
Abstract: A series of isoflavone functionalized 3, 4‐dihydro‐1, 3‐oxazine hybrids was synthesized in good to excellent yields through a Mannich‐type condensation cyclization reaction of 6‐chloro‐7‐hydroxy‐3‐(2‐methoxy‐phenyl)‐chromen‐4‐one or 6‐chloro‐7‐hydroxy‐3‐(2‐methoxy‐phenyl)‐chromene‐4‐thione with formaldehyde and primary amines. After spectroscopic characterization, these newly prepared hybrids were evaluated for their antibacterial activities against two of each Gram positive ( Staphylococcus aureus and Bacillus subtilis ) and Gram negative ( Escherichia coli and Pseudomonas aeruginosa ) bacterial strains. Among the screened compounds, dihydro[1, 3]oxazine‐fused 4‐thionoisoflavones(9 b and9 c ) exhibited potent inhibitory activity against all the tested bacterial species. Moreover, compound 9 b possessed most promising antibacterial activity against P. aeruginosa and B. subtilis with MIC 16 μg/mL and S. aureus and E. coli with MIC 32 μg/mL. Further, 9 b demonstrated better efficacy (MIC=16 μg/mL) than the standard drug ampicillin (MIC=32 μg/mL) against P. aeruginosa and it also found to be equipotent (MIC=16 μg/mL) as ampicillin against B. subtilis . Considering the disk diffusion and synergistic studies, 9 b emerged asmost active compound showing potent activity against all the tested bacterial strains. In addition, no significant hemolysis or cytotoxicity was observed towards human embryonic kidney (HEK293)cells as well as Galleria mellonella larvae (in vivo). Hence, compound 9 b has potential to be further explored alone and in combination with ampicillin as a next generation antibacterial agent. Abstract : Diverse dihydro[1, 3]oxazine‐fused isoflavone and 4‐thionoisoflavone derivatives were synthesized in search of potent antibacterial agents. On biological evaluation, 4‐thionoisoflavone tethered 3, 4‐dihydro[1, 3]oxazine (9 b ) appeared as a lead molecule and exhibited potent inhibitory activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa . In addition, the compound 9 b demonstrated synergistic effect when used in combination with ampicillin and has no significant cytotoxicity towards human embryonic kidney (HEK293) cells as well as Galleria mellonella larvae.